Analisis Semiotika Nilai-Nilai Dakwah Islam dalam Series Ms. Marvel - Elsa Novariani Ramadhani; Rodliyah Khuza’i; Muhammad Fauzi Arif (UNISBA Press, 2024)
Abstract. This research uses Charles Sanders Pierce's semiotic analysis method. The research objective is to determine the semiotic content and find out the Islamic values of faith, sharia, and morals contained in the Ms. Marvel series. The content of Islamic values in this series discusses about: the value of faith in general discusses a lot about faith in Allah SWT such as saying bismillah, And beware of what others say. Meanwhile, Sharia values in the Ms. Marvel series generally show jinayah laws such as prohibition of wearing tight clothing, prohibition of stealing, prohibition of drinking alcohol, wearing hijab, and obeying the rules, and the moral values contained in the Ms. Marvel series show relationships that occur in daily life such as saying prayers before eating, shodaqoh, prohibition of going out at night, lying to parents, manners in assembly, leadership, apologizing, prohibition of discrimination or racism, and tolerance. Abstrak. Penelitian ini menggunakan analisis semiotika Charles Sanders Peirce. Tujuan dari penelitian ini adalah untuk mengetahui analisis semiotika dan nilai-nilai Islami akidah, syariah, dan akhlak yang terkandung dalam series Ms. Marvel. Kandungan nilai-nilai Islami dalam series ini membahas mengenai: nilai akidah secara umum banyak membahas mengenai keimanan kepada Allah SWT seperti mengucapkan bismillah, dan waspada terhadap apa yang orang lain katakan, sedangkan nilai-nilai syariah dalam series Ms. Marvel secara umum memperlihatkan hukum-hukum jinayah seperti larangan menggunakan pakaian ketat, larangan mencuri, larangan minum alkohol, menggunakan hijab, dan menaati peraturan, dan nilai-nilai akhlak yang terkandung dalam series Ms. Marvel memperlihatkan hubungan yang terjadi dalam kehidupan sehari-hari seperti mengucapkan do’a sebelum makan, shodaqoh, larangan keluar malam-malam, berbohong pada orang tua, adab dalam majelis, kepemimpinan, meminta maaf, larangan diskriminasi atau rasisme, dan toleransi.